Comparison of whole-body vibration training and quadriceps strength training on physical function and neuromuscular function of individuals with knee osteoarthritis: A randomised clinical trial - Zhangqi Lai; Seullee Lee; Yiyang Chen; Lin Wang (Elsevier, 2021)
Background/Objective: Knee osteoarthritis (KOA) is one of the leading causes of global disability, which causes knee pain, stiﬀness and swelling. Impaired neuromuscular function may cause joint instability, alignment changes and knee stress, which leads to the progression of KOA. Whole-body vibration (WBV) training is considered to improve pain and functional mobility effectively. However, few studies have investigated the therapeutic effect of WBV on neuromuscular function in KOA. Methods: A single-blinded, randomised, controlled trial was performed on 81 participants diagnosed with KOA. The participants were randomised into three groups: (1) WBV group, in which participants performed strength training (ST) with vibration exposure for 8 weeks; (2) ST group, in which participants performed ST without vibration for 8 weeks; and (3) health education (HE) group, in which participants received a HE for 8 weeks. The visual analogue scale for knee pain, isokinetic muscle strength test, proprioception test, Timed Up and Go test (TUG) and 6-min Walk Distance test (6MWD) were performed before and after the interventions. Results: No significant difference was found on pain, proprioception, TUG and 6MWD. A significant interaction effect was found in isokinetic muscle strength between groups. Further analysis showed that compared with the HE group, the WBV group exhibited significantly greater improvement in isokinetic muscle strength (peak torque [PT] of extensors, p < 0.01, 95% CI = 0.11-0.33 Nm/kg; PT of flexors, p = 0.01, 95% CI = 0.02-0.19 Nm/kg; peak work [PW] of extensors, p < 0.01, 95% CI = 0.12-0.75 W/kg). In addition, compared with the ST group, the muscle strength of the WBV group (PT of extensors, p < 0.01, 95% CI = 0.10-0.32 Nm/kg; PW of extensors, p < 0.01, 95% CI = 0.09-0.71 W/kg) improved significantly. Conclusion: Our findings suggested that adding WBV training to ST might benefit muscle strength around the knee joint in patients with KOA.